Gangguan Berbahasa Afasia Motorik pada Ny. Nurhayati - Muftiathul Huda; Leni Syafyahya; Alex Darmawan (Puitika, 2023)
The purpose of this study was to describe and explain the verbal language disorders in patients with motor aphasia in cases of NH. The stages in the research, namely the first stage of providing data used observation and analysis methods, case study methods, and natural observation methods. Follow the see method. The listening method uses tapping techniques as a basic technique and advanced techniques, namely the Libat Cakap (SLC) technique, the Libat Cakap Free Listening technique (SBLC), recording techniques, and note taking techniques. At the data provision stage, the technique of providing an image to NH was also carried out. the second stage, namely the data analysis stage, used the articulatory equivalent method and the translational equivalent method with the determining element sorting technique (PUP) as the basic technique and the follow-up technique is the differential linking technique (HBB). In the methods and techniques of presenting the results of data analysis, informal presentation methods are used. The results of the study showed that NH experienced problems in terms of speaking, naming, and repeating. Interference in terms of speech such as short and spontaneous speech (sparse output), speech that is not fluent so that it requires duration (pauses), and speech that is wrong in its pronunciation. Disturbances in naming, such as NH's inability to name objects, names of days, names of prayers, and names of family members. Problems with repetition, such as the inability of NH to repeat words that have the letter "R" and to repeat complex sentences.